Weak Markets, Strong Teachers - Markus Nagler; Marc Piopiunik; Martin R. West (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Can policymakers hire more effective teachers by increasing the relative economic benefits of teaching? We investigate this question by exploiting business cycle conditions at career start as a source of exogenous variation in the outside labor market opportunities of potential teachers. Using administrative data on 33,000 teachers in Florida s public schools, we find that teachers who entered the profession during recessions have significantly higher math value-added measures than teachers who entered the profession during non-recessionary periods. We explain these findings with a simple Roy model of occupational choice. Results are not driven by differential attrition or by any single recession.
Keywords: J24; I20; H75; 330